2019
DOI: 10.1192/bjo.2019.92
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers to collaboration in the mental health system in Sabah, Malaysia: towards a theory of collaboration

Abstract: BackgroundThe systems that help people with mental disorders in Malaysia include hospitals, primary care, traditional and religious systems, schools and colleges, employers, families and other community members. AimsTo better understand collaboration between and within these systems and create a theoretical framework for system development. MethodA total of 26 focus groups and 27 individual interviews were undertaken with patients, carers, psychiatric hospital staff, primary care and district hospital staff, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This course was started as part of an action research project to improve collaborative practice in the Malaysian mental health system. Qualitative research had shown that the system was frequently not working collaboratively, in that patients were not forming a therapeutic alliance with any of their healthcare providers and a hierarchical culture meant that staff were not collaborating well with each other ( 7 ). The techniques are small discrete micro-skills that have been extracted from the several psychotherapies and simplified for delivery.…”
Section: Ubpimentioning
confidence: 99%
“…This course was started as part of an action research project to improve collaborative practice in the Malaysian mental health system. Qualitative research had shown that the system was frequently not working collaboratively, in that patients were not forming a therapeutic alliance with any of their healthcare providers and a hierarchical culture meant that staff were not collaborating well with each other ( 7 ). The techniques are small discrete micro-skills that have been extracted from the several psychotherapies and simplified for delivery.…”
Section: Ubpimentioning
confidence: 99%
“…Barriers to multidisciplinary care included lack of time, difficulty reaching other clinicians, lack of personal relationships with other clinicians, lack of information and feedback loops, discrepancies in medication list, lack of clarity on accountability and autonomy, relatedness, motivation and resources, and the potential cost of care without reciprocation [ 33 , 51 ]. Furthermore, mismatch and relationships of providers hindered multidisciplinary care coordination (e.g., general practitioners and pharmacists, professional groups), disputes, physician-centred power, damage of shared care, resistance to interprofessional collaboration based on knowledge-power relations, and lack of knowledge on interprofessional interference [ 26 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Malaysia, community factors of continuity of care include collaborative behaviours, motivation towards a common goal or value, autonomy, relatedness (e.g., trusting, understanding and caring about the other), resources (e.g., competence, time, physical resources and opportunities), and motivation for collaboration (weighing up the personal costs versus benefits of acting collaboratively) patients [ 51 ]. Nonetheless, inefficient communication with healthcare providers, a slow and faltering process of institutional change with a make-or-buy decision, and efforts barred patient access to care and outcomes [ 35 , 49 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…There have been a few successful partnerships with traditional healers to expand access to health screening programmes in medically pluralistic contexts. These initiatives have included trainings for healers to deliver counselling and facility referral for HIV (Homsy & King, 1996 ; King & Homsy, 1997 ), tuberculosis (Peltzer, Mngqundaniso, & Petros, 2006 ) or malaria testing (Makundi, Malebo, Mhame, Kitua, & Warsame, 2006 ), provide mental healthcare (Shoesmith et al, 2020 ; Solera-Deuchar, Mussa, Ali, Haji, & McGovern, 2020 ) or to increase uptake of prenatal care (Audet et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%